2018
DOI: 10.29219/fnr.v62.1323
|View full text |Cite
|
Sign up to set email alerts
|

Nobiletin inhibits breast cancer via p38 mitogen-activated protein kinase, nuclear transcription factor-κB, and nuclear factor erythroid 2-related factor 2 pathways in MCF-7 cells

Abstract: IntroductionBreast cancer is one of the most commonly diagnosed cancers in women, with a high mortality rate.ObjectiveIn the present study, we evaluated the anticancer effect of nobiletin, a flavone glycoside, on the breast cancer cell line MCF-7.ResultCell viability and proliferation decreased and cell morphology changed from diamond to round after being treated with nobiletin. Nobiletin induced apoptosis of breast cancer MCF-7 cells via regulating the protein expression of Bax, Bcl-2, cleaved caspase-3, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 49 publications
3
41
0
Order By: Relevance
“…21 It may induce apoptosis and inhibit cell migration via MAPK and/or MAPK/AKT related pathways. 22,23 Similar anti-proliferative effects have been observed in high tumor grade MDA-MB-231 23 and MDA-MB-468 human breast cancer cells following treatment with nobiletin. 24 Nobiletin has also been shown to inhibit growth of metastatic nodules in the lungs of mice via the TGF-β1/SMAD3 pathway 25 and decrease cell migration, angiogenesis, tumor formation, and progression in the bone osteosarcoma cell line U2OS via ERK and JNK pathways.…”
supporting
confidence: 56%
See 3 more Smart Citations
“…21 It may induce apoptosis and inhibit cell migration via MAPK and/or MAPK/AKT related pathways. 22,23 Similar anti-proliferative effects have been observed in high tumor grade MDA-MB-231 23 and MDA-MB-468 human breast cancer cells following treatment with nobiletin. 24 Nobiletin has also been shown to inhibit growth of metastatic nodules in the lungs of mice via the TGF-β1/SMAD3 pathway 25 and decrease cell migration, angiogenesis, tumor formation, and progression in the bone osteosarcoma cell line U2OS via ERK and JNK pathways.…”
supporting
confidence: 56%
“…23 Multiple experiments showed that nobiletin downregulates CD36, STAT3, pSTAT3, MMPs, and NF-κB proteins, among others in MCF7 cells. 22,23,30 Colony areas were concomitantly increased and decreased with dose in U2OS and MDA-MB-231 cells, respectively, while MCF7 was affected only at the highest concentration used. Previous studies showed that nobiletin-treated breast cancer cells had reduced cell proliferation in largely two-dimensional assays.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Currently, NBL possesses a variety of physiological activities. It has been reported that NBL can induce apoptosis of human breast cancer cells (Liu et al 2018), inhibit the viability of human renal carcinoma cells (Wei et al 2019) and exert or not exert antileukemic effects (Chen et al 2018). Combination of different drugs can affect the bioavailability of drugs and the anticancer effect.…”
Section: Introductionmentioning
confidence: 99%